A dedicated Y‐shaped percutaneous ECMO cannula for femoral 2‐in‐1 vascular access during high‐risk procedures. Issue 5 (1st October 2020) - Modine, Thomas; Vincent, Flavien; Delhaye, Cédric; Van Belle, Eric
Abstract: High‐risk transcatheter procedures requiring hemodynamic support are growing and require multiple vascular access that may be challenging in cases of peripheral artery disease or lack of radial access and exposure to a higher risk of vascular complications. We report the novel utilization of a Y‐shaped arterial extracorporeal membrane oxygenation (ECMO) cannula used as a single femoral access to perform percutaneous coronary intervention (PCI) and aortography during high‐risk transcatheter aortic valve replacement (TAVR). The utilization of this 2‐in‐1 ECMO cannula may simplify vascular access and reduce vascular and bleeding complications during high‐risk ECMO‐supported transcatheter procedures.